2011
DOI: 10.1021/ja205868b
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a Donor–Acceptor Nanotube. A Strategy To Create Bicontinuous Arrays

Abstract: The self-assembly of bolaamphiphile 1 into nanotubes containing a nanostructured electron donor/acceptor heterojunction is reported. In 10% MeOH/H(2)O, the tetraphenylporphyrin (TPP) and 1,4,5,8-naphthalenetetracarboxylic acid diimide chromophores engage in strong J-type π-π interactions within monolayer rings that further stack into the nanotube assemblies. In 10% MeOH/H(2)O at pH 1 or 11 or in pure MeOH, assembly is driven exclusively by the TPP ring, leading to the formation of nonspecific, unstructured agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 51 publications
(34 reference statements)
2
62
0
2
Order By: Relevance
“…23,24,25 Scheme 1. AFM, TEM and SEM experiments indicate that the regiochemistry of the substitution on the core of the naphthalene diimide, together with coordination of the terpyridine ligand to different metals, strongly influences the morphologies of the resulting metallosupramolecular polymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23,24,25 Scheme 1. AFM, TEM and SEM experiments indicate that the regiochemistry of the substitution on the core of the naphthalene diimide, together with coordination of the terpyridine ligand to different metals, strongly influences the morphologies of the resulting metallosupramolecular polymers.…”
mentioning
confidence: 99%
“…23,24,25 Scheme 1. 13 However, bay-substituted PDIs must twist out-of-plane in order to avoid steric issues between the PDI ring and the substituent, 15 unlike the planar core-substituted NDI groups, and therefore do not undergo π-stacking as well to form higher order structures.…”
mentioning
confidence: 99%
“…Recently, Tu et al reported self-assembly of nanotubes from NDI-TPP-NDI bolaamphiphile 23 (figure 24) [62]. When the aqueous solution of 23, containing 10% MeOH, was aged for 2-3 days, well-organized, micrometer-long nanotubes formed with a diameter and wall thickness of 13.6 and 4.6 nm, respectively.…”
Section: Porphyrin-perylene and Naphthalene Diimide Dyadsmentioning
confidence: 99%
“…Organic solid-state photoactive chromophores have received increasing attention during the past 20 years due to their unique optical properties and promising optoelectronic applications in the fields of lasers [1,2], sensors [3][4][5][6][7], and biological imaging [8][9][10]. Meanwhile, more and more research attention has been paid to molecule-based micro/nanomaterials in chemistry, materials science, and pharmaceutics/medicine [11][12][13][14], since micro/nanomaterials exhibit unique properties superior to those of their bulk counterparts [15,16], owing to their surface effect, quantum size effect [17,18], and so on.…”
Section: Introductionmentioning
confidence: 99%